Candidemia Distribution, Associated Risk Factors, and Attributed Mortality at a University-Based Medical Center - Conde-Rosa, Ana; Amador, Rosana; Pérez-Torres, Doris; Colón, Eileen; Sánchez-Rivera, Carlos; Nieves-Plaza, Mariely; González-Ramos, Michelle; Bertrán-Pasarell, Jorge (Puerto Rico Health Sciences Journal, 2010)
Candida is the fourth most common cause of nosocomial bloodstream infections (BSI), being Candida albicans the most common species. This study evaluated the distribution of Candida spp isolates at a tertiary care medical center. The associated factors and outcome of patients with candidemia at the Puerto Rico Medical Center (PRMC) were evaluated. Laboratory data from May 2005 to April 2006 was reviewed. Blood cultures reported as positive for Candida spp were identified and records were reviewed. Two hundred and four blood cultures were reported with Candida spp, corresponding to 85 different episodes of candidemia in 82 patients: 3 patients presented more than one candidemia episode with two different Candida spp. In seventy-two percent (61/85) of candidemia episodes, the organism isolated was a non-albicans Candida, being C. parapsilosis the most common species isolated with 49% (42/85). Sixty five records were evaluated; of which 45 cases were reviewed (20 cases were excluded from the study due to incomplete information). The predominant factors identified were being on broad spectrum antibiotics 95.6% (43/45), central catheter placement 97.8% (44/45), mechanical ventilation 64.4% (29/45), and urinary catheter placement 73.3% (33/45). The mortality among the reviewed cases was 48.9% (22/45). [P R Health Sci J 2010;1:26-29]